Perceptions of student nurses regarding the delivery of quality nursing care in katutura health centre, Windhoek and khomas region - Amukugo, Hans Justus; Mathews, AIno (International Journal of Advanced Nursing Studies, 2015)
The purpose of this study is to explore and describe the perceptions of nursing students regarding the delivery of quality nursing care in Katutuura Health Centre, Windhoek, and Khomas Region.A qualitative, exploratory, descriptive and contextual research designs were used in this study. An individual interview was conducted on ten (10) 4th year nursing students at UNAM main campus with regard to the delivery of quality nursing care. The data showed that most students expressed shortage of staff, high number of patient attendance, insufficient equipment and insufficient time as factors that affect the delivery of quality nursing care. Possible interventions regarding resource management should be put into consideration, where extra nursing staffs needed to be trained and distributed among hospitals and clinics in Namibia.